New insights into Paleoproterozoic tectonics of the Yangtze Block in the context of early Nuna assembly: Possible collisional granitic magmatism in the Zhongxiang Complex, South China - Wang, Kai; Dong, Shuwen (Precambrian research, 2019)
•Circa 2.0–1.93 Ga S-type granitic magmatism in the Zhongxiang Complex.•Late Paleoproterozoic tectonic transition from collisional convergence to post-collisional extension.•Possible internal assembly of the Yangtze Block during the early Nuna accretion phase. The newly discovered Zhongxiang Complex preserving extensive Paleoproterozoic granitoids plays a pivotal role in understanding the early tectonic processes of the Yangtze Block, South China, in the context of the Nuna supercontinent cycle. New zircon U-Pb age and Hf-isotope coupled with whole-rock chemical and Nd-isotope results from three granitic intrusions in the southern Zhongxiang Complex document a magmatic record of significant late Paleoproterozoic tectonic convergence in the region. Geochronological data show that granites from these intrusions were emplaced in a relatively long period at 2.0–1.93 Ga. The granites have variably high SiO2 contents of 74.01–77.19 wt%, and are weakly to strongly peraluminous with high ASI (alumina saturation index) values (>1.05). They are generally magnesian, showing fractionated S-type granite affinities. They have negative zircon εHf(t) of −9.69 to −17.11 and negative whole-rock εNd(t) of −7.43 to −11.69, corresponding to two-stage Hf model ages of 3.24–3.67 Ga and two-stage Nd model ages of 3.0–3.37 Ga, respectively, indicating a derivation of their parental magmas from remelting of ancient crustal components (i.e., the Yangpo “Group” paragneisses). The moderate to strong LREE/HREE fractionation ((La/Yb)N > 22, average 73.15) and the relatively low Sr/Y and negative Eu anomalies of the least felsic samples further imply a residual assemblage probably involving both garnet and plagioclase, corresponding to middle-lower crustal levels. This magmatic event most likely occurred at a convergent continental margin related to continental collision, which, in conjunction with broadly coeval metamorphism and the succeeding A-type granitic magmatism in the region, delineates a possible late Paleoproterozoic tectonic transition from compression to extension, signifying a cycle from collision (2.0–1.93 Ga) to post-collision (1.85 Ga) in the Zhongxiang Complex. Such a collisional orogenesis was potentially linked to the Paleoproterozoic internal assembly of the eastern part of the Yangtze Block, presumably as part of the early assembly of the Nuna supercontinent.